Effect of Host Plants on the Growth and Development of the Polyphagous Defoliator Cricula Trifenestrata Helfer (Lepidoptera: Saturniidae) - Gharde, S. K.; Chaudhuri, N. (International Journal of Bio-resource and Stress Management, 2017)
The effect of four host plant species [Mango, Mangifera indica L., Cinnamon, Cinnamomum cassia, Cashew, Anacardium occidentale L., Som, Machilus bombycina King], on biology of the polyphagous defoliator Cricula trifenestrata Helfer (Lepidoptera: Saturniidae) was studied. C trifenestrata completed four generations in a year. The generation time changed according to temperature and relative humidity. Biological parameters of the caterpillar differed significantly among the host plants and in different generations completed in a year. The larval developmental period was longest 42.17−43.81 days in January-March generation. The overall developmental duration was shortest in March-May generation and longest in May-October generation. The generation time was shorter on M. bombycina (85.57−145.12 days and 86.35−149.56 days for males and females, respectively) and M. indica (84.97−143.63 days and 87.27−148.55 days for males and females, respectively), whereas it was longest on C. cassia (88.56−147.93 days and 90.28−153.21 days for males and females, respectively). The adult longevity was longest (3.23−4.15 days) in the October-January generation. The total number of eggs per female for all the generations varied between 62.34 and 122.30 and it was highest on M. bombycina and M. indica in October-January generation. Degree days per generation changed between 943.74 DD and 1971.08 DD. Biological properties of the pest changed in each generation. In this study, the biological parameters of C. trifenestrata were determined for different host plants in different generations and this data can be used as an important step towards developing successful Integrated Pest Management strategies.